Ischemia Elicits a Coordinated Expression of Pro-Survival Proteins in Mouse Myocardium - Deborah Lyn; Shaojia Bao; Nicole A. Bennett; Xiaowei Liu; Nerimiah L. Emmett (The Scientific World Journal)
Cardiomyocytes are post-mitotic, long-lived cells until disruptions to pro-survival factors occur after myocardial ischemia. To gain an understanding of the factors involved with ischemic injury, we examined expression changes in pro-survival and opposing pro-apoptotic signals at early and chronic periods of ischemia using an in vivo murine model. Alterations of pro-survival proteins such as the inhibitor of apoptosis protein on chromosome X (xIAP) and the apoptotic repressor protein (ARC) have not been evaluated in a murine model of cardiac ischemia. Early ischemia (1 day) resulted in a 50% reduction in ARC protein levels relative to sham-operated left ventricles, without significant changes in the expression of xIAP or other pro-survival factors. In contrast, a deficiency of xIAP expression was found in cardiac infarcts starting after 1 week, concomitant with significant evidence of apoptotic cell death and an up-regulation of pro-apoptotic signals including Bax, tumor necrosis factor-a, and caspase-8 activation. Chronic ischemia (after 2 weeks) was associated with elevated levels of other pro-survival factors such as Bcl-xL and the phosphorylated form of Akt, as part of the adaptive remodeling of the myocardium. Altogether, these findings suggest that strategies to increase IAP expression may promote myocyte survival after chronic ischemia.